Keharmonisan Antara Sang Khalik dan Seluruh Makhluk - Najamuddin, Najamuddin (Tasamuh: Jurnal Studi Islam, 2015)
Plurality is a diversity. The pluralism is the existence of a plurality of the laws. Plurality is defined as a society which has difference from each other, both in terms of economic level, ideological faith and ethnicity. But it was not considered a feud, but it has straps that bind the union. Plurality of God’s creation (creature), a sign ofoneness of God